EFEKTIVITAS PENGENDALIAN INTERNAL PENJUALAN KREDIT RUMAH PADA PERUM PERUMNAS CABANG KALIMANTAN TIMUR - Paung, Yustiani Manasye (EKONOMIA, 2014)
The purpose of this paper is to investigate and analyze the control in the sale of home loans in East Kalimantan branch Perumnas.In accordance with the purposes of this study the main issues pointed out "Is the internal control of credit sales Perumnas East Kalimantan branch has been carried out effectively."Based on the subject matter, the proposed hypothesis is as follows: "Internal control sale of home loans Perumnas East Kalimantan branch has not been effective".The analytical tool used in this study is the authors compare the internal control system of internal control systems theory with PerumnasAfter going through the stages of research, analysis and discussion in the know that the internal control of credit sales at Perumnas East Kalimantan branch has gone well, this in view of the results of research to get the "74%" which means the application of internal control is effective in supporting the granting procedure credit.Thus the hypothesis that the proposed sale of the internal control home loans Perumnas East Kalimantan branch has not been effectively rejected.